2020
DOI: 10.17576/pengurusan-2020-60-01
|View full text |Cite
|
Sign up to set email alerts
|

To Buy or Not to Buy? Consumers’ attitudes and Purchase Behavior for Organic Food in Malaysia

Abstract: Organic products demand is increasing due to the awareness of the health benefits and nutritional values attached to these produces. However, in Malaysia, the organic industry is relatively small with more than 60% of the organic products being imported from overseas. Given the importance of this niche sector to the agriculture sector, marketers should understand how the consumers make decisions towards organic products. This study investigated the Malaysian organic purchasers on what affects them in their buy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 50 publications
(58 reference statements)
0
0
0
Order By: Relevance
“…Malaysia is one of the nations in the Asia-Pacific region with excellent potential for the development of organic food (Nathan et al, 2021). With the country's organic product consumption demand estimated at more than RM20 million per year with a growth rate of at least 12.4% annually (Cheng et al, 2020;Suhaimee, Ibrahim & Abd Wahab, 2016), it has become one of the primary drivers of Malaysia's economic growth in the service sector (Salmuni et al, 2020). While the Department of Agriculture Malaysia (DOAM) (2019) reported that people's acceptance of organic food products is increasing dramatically, the COVID-19 outbreak starting end of 2019 has severely affected the marketplace environment including retail outlets.…”
Section: Introductionmentioning
confidence: 99%
“…Malaysia is one of the nations in the Asia-Pacific region with excellent potential for the development of organic food (Nathan et al, 2021). With the country's organic product consumption demand estimated at more than RM20 million per year with a growth rate of at least 12.4% annually (Cheng et al, 2020;Suhaimee, Ibrahim & Abd Wahab, 2016), it has become one of the primary drivers of Malaysia's economic growth in the service sector (Salmuni et al, 2020). While the Department of Agriculture Malaysia (DOAM) (2019) reported that people's acceptance of organic food products is increasing dramatically, the COVID-19 outbreak starting end of 2019 has severely affected the marketplace environment including retail outlets.…”
Section: Introductionmentioning
confidence: 99%